Investigation of charge ratio variation in mRNA – DEAE-dextran polyplex delivery systems. (February 2019) - Siewert, C.; Haas, H.; Nawroth, T.; Ziller, A.; Nogueira, S.S.; Schroer, M.A.; Blanchet, C.E.; Svergun, D.I.; Radulescu, A.; Bates, F.; Huesemann, Y.; Radsak, M.P.; et al.
Abstract: mRNA pharmaceuticals represent a new class of therapeutics, with applications, in cancer vaccination, tumour therapy and protein substitution. Formulations are required to deliver messenger RNA (mRNA) to the target sites where induction of genetic transfection following receptor mediated cell uptake & translation is required. In the current study, the cationic polysaccharide diethylaminoethylen (DEAE) – Dextran was selected as a model system carrier for the investigation of polyplex nanoparticle formation together with mRNA as a function of the molar ratio of the components. The structure of the mRNA/Dextran colloids was investigated as a function of the polymer-to-mRNA ratio and correlated with the biological activity determined by cellular transfection with luciferase coding mRNA. Dynamic light scattering (DLS), small angle x-ray scattering (SAXS), and small angle neutron scattering (SANS) with deuterium contrast variation were used to achieve structural insight into the systems. Similarly to previously investigated lipid based systems, colloidally stable particles with confined size were obtained with either excess of positive or negative charge. Highest activity was obtained with positive charge excess. From the scattering experiments information on the internal organization inside the polymer/mRNA systems was derived. Indication for the presence of structural elements in the length scale of ten to 20 nm were found in the excess of dextran, which could be due to either excess or particulate polymer. Information on the molecular organization of the mRNA nanoparticle products may provide a valuable basis for defining critical quality attributes of drug products for pharmaceutical application. Graphical abstract: Image 1